Superovulatory responses of eCG and live births foil owing surgical embryo transfer in Marwari ewes - PUROHIT, G N; KUMAR, DINESH; YADAV, R C; GOSWAMI, PRAVEEN; BISSA, PRASHANT; GARG, NARESH; SHARMA, S S (The Indian Journal of Animal Reproduction, 2023)
Multiple ovulation and embryo collection (n = 8) was done in Marwari ewes followed by their transfer to synchronisedrecipients (n = 7) Donor ewes were superovulated by injecting 1000 lU of eCG on day 12 of a progesterone implant under two groups.Group I (n = 4) received a commercially available progestagen implant CIDR-G whereas in Group n (n = 4) ewes received anindigenously prepared implant. Ewes were induced to estrus by a PG injection and mated to fertile rams at estrus. Embryos werecollected surgically on day 6, their ovarian response recorded and embryos transferred surgically. Only 75% (3/4) ewes responded inboth the groups . The number of CL/ewe, total ova recovery rate, fertilized eggs/ewe and number of morula/blastocysts/ewe were7.0±2.51 , 4.66±2.66, 3.66±2.18 and 3.0±1.52 in group I and 10.0±5.13, 9.34±4.37, 7.34±4.48 and 9.34±2.02 in Group II.Statistically all these were non significantly different except for the total ova recovery rate which was significantly higher (P < 0.05)in Group II indicating thereby that locally made sponges can replace commercial implants of progestagens. Three pregnancies andlive births resulted from transfer of 12 embryos to 7 recipients.
Keywords: eCG; embryo transfer; ewes; superovulation